Chicoric acid does not restore palmitate-induced decrease in irisin levels in PBMCs of newly diagnosed patients with T2D and healthy subjects - Arab Sadeghabadi, Zahra; Abbasalipourkabir, Roghayeh; Mohseni, Roohollah; Ziamajidi, Nasrin (Archives of physiology and biochemistry, 2022)
Targeting irisin as a myokine/adipokine is a new therapeutic approach in the improvement of insulin-resistance (IR) during type 2 diabetes (T2D). In present study we evaluated the effects of palmitate and chicoric acid (CA) on irisin production in peripheral blood mononuclear cells (PBMCs) of patients with T2D. This study performed on 20 newly diagnosed patients with T2D and 20 healthy subjects. PBMCs treated with palmitate and CA. PPARGC1A and FNDC5 genes expression assessed using qRT-PCR. Irisin levels in cell culture medium measured by ELISA. Palmitate decreased PPARGC1A and FNDC5 genes expression, as well as irisin levels in PBMCs from T2D and healthy volunteers. CA significantly restored palmitate-induced decrease in PPARGC1A gene expression in PBMCs of healthy subjects. Although, FNDC5 gene expression and irisin levels were not induced significantly by CA. In conclusion, palmitate decreases irisin production through down-regulation of PPARGC1A and FNDC5 expressions. However, CA does not effect on irisin pathway. Key points Palmitate reduced PPARGC1A and FNDC5 genes expression, as well as irisin secretion in PBMCs. Palmitate-induced decrease in PPARGC1A gene expression significantly has been reversed by CA in PBMCs of healthy subjects. CA did not return palmitate-decreased in FNDC5 gene expression and irisin levels in PBMCs.